De Apographo Quodarn Matritenst * Moa~íówoq FIcpi Fuvctuccíwv flaOéSv - Floristán Imizcoz, José M. (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 1991)
The arranging of the personal archives of Infante Gabriel de Borbón has provided us with a new manuscript of Mosquion’s Gynaecology. Mosquion is known since the Renaissance as a Greek physician of the late period, until V. Rosé ir’ 1881 drew our attention to the true nature of bis work as a translation of a latin original. The author of this essay takes as starting po¡nt a photocopy of the aforementioned work -—the original being unluekily lost nowadays--—, describes the manuscript. examines its relationship with the most important codices of the Latin original and studies its most remarkable linguistic léatures, which clearly confirm V. Rose´s conclusions.